2011
DOI: 10.1136/jnis.2011.004689
|View full text |Cite
|
Sign up to set email alerts
|

Angioplasty and stent placement for complete occlusion of the vertebral artery secondary to giant cell arteritis

Abstract: Giant cell arteritis (GCA) is the most common form of systemic vasculitis in adults. Patients usually present with headache and visual symptoms, and have an elevated erythrocyte sedimentation rate. It has been reported that 3-4% of patients with GCA develop ischemic events secondary to vertebral artery stenosis or occlusion. The mainstay of therapy of GCA is high dose steroid and/or methotrexate. A case is described of a patient who initially presented with intermittent double vision, mild headache and unremar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 12 publications
0
20
0
Order By: Relevance
“…To date, only two cases of endovascular treatment on patients with GCA with intracranial stenosis have been described. Chausson et al described a case of GCA with preocclusive bilateral carotid stenosis in which they carried out angioplasty and stenting. Shah et al reported another case with complete occlusion of the V4 segment of the right vertebral artery treated with angioplasty and stenting.…”
Section: Discussionmentioning
confidence: 99%
“…To date, only two cases of endovascular treatment on patients with GCA with intracranial stenosis have been described. Chausson et al described a case of GCA with preocclusive bilateral carotid stenosis in which they carried out angioplasty and stenting. Shah et al reported another case with complete occlusion of the V4 segment of the right vertebral artery treated with angioplasty and stenting.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment is challenging and, in addition to established medical treatment strategies of GCA and ischemic stroke, may necessitate rescue endovascular treatment. While clinically not successful in our patient, neurological improvement after angioplasty and stenting has been reported in a similar clinical situation [4]. Arterial dissection was found to be causative for acute bilateral vertebral artery occlusion in our patient.…”
Section: Introductionmentioning
confidence: 74%
“…The vertebrobasilar circulation is affected most frequently [1][2][3]. The reported cases were similar in the clinical presentation with typical clinical symptoms of GCA (age >50 years, new onset of headache, elevated inflammatory parameters and some with jaw claudication and/or visual deterioration) and a subsequent neurological worsening [3][4][5]. The majority of events occur before or early after initiation of corticosteroid treatment [2,3].…”
Section: Introductionmentioning
confidence: 97%
“…We have only found balloon dilatation and stenting described before in three single cases (11)(12)(13). The use of stent retrievers in the treatment of cerebral vasospasm in patients with subarachnoid hemorrhage has been described recently (14) and the technique was adopted in cases due to failure of performing balloon angioplasty.…”
Section: Discussionmentioning
confidence: 99%